Synthesis of quinolinyl based pincer copper (II) complexes: an efficient catalyst system for Kumada coupling of alkyl chlorides and bromides with alkyl Grignard reagents - Pandiri, Hanumanprasad; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2018)
Quinolinamide-based pincer copper(ii) complexes, (N),(N),(N)-{C9H6N-(-N)-C(O)CH2NEt2}CuX [((NNN2Et)-N-Q)CuX (X = Cl, 2; X = Br, 3; X = OAc, 4)], were synthesized by the reaction of ligand ((NNN2Et)-N-Q)-H (1) with CuX2 (X = Cl, Br or OAc) in the presence of Et3N. The reaction of ((NNN2Et)-N-Q)-H with CuX (X = Cl, Br or OAc) also afforded the Cu(ii) complexes 2, 3 and 4, respectively, instead of the expected Cu(i) pincer complexes. The formation of Cu(ii) complexes from Cu(i) precursors most likely occurred via the disproportionation reaction of Cu(i) into Cu(0) and Cu(ii). A cationic complex [((NNN2Et)-N-Q)Cu(CH3CN)]OTf (5) was synthesized by the treatment of neutral complex 2 with AgOTf. On the other hand, the reaction of ((NNN2Et)-N-Q)-H (1) with [Cu(MeCN)(4)]ClO4 produced cationic Cu(i) complex, [((NN)-N-Q(H)N-2(Et))Cu(CH3CN)]ClO4 (6), in good yield. All complexes 2-5 were characterized by elemental analysis and HRMS measurements. Furthermore, the molecular structures of 2, 3 and 4 were elucidated by X-ray crystallography. Complex 4 crystallizes in a dimeric and catemeric pattern. The cationic complex 5 was found to be an efficient catalyst for the Kumada coupling reaction of diverse nonactivated alkyl chlorides and bromides with alkyl magnesium chloride under mild reaction conditions.